The Implications of Indo-Pacific Strategies for Bangladesh Challenges and Options - Ahmed, Bashir (Asian Studies, 2023)
The Indo-Pacific Strategies (IPS) is still in development, and participation in something that does not yet exist is challenging. However, we notice that many things are common when we examine the Indo-Pacific region. There are distinctions between Chinese and American soft power. China’s soft power manifests through constructing roads, ports, bridges, and schools, whereas the United States focuses mostly on military assets. Some fear that the region would fall victim to the Thucydides Trap, in which a rising state forces an existing power into a conflict that results in the demise of the established power. The Indo-Pacific will play a crucial role in the geostrategic and geo-marine strategic battle between developing nations; it elevates maritime thought in our strategic discourse and is a crossroads of geopolitics, geo-strategy, geo-economics, and geo-energy. As a result, the Indian Ocean has become the epicenter of all geostrategic strife. Bangladesh’s location on the Bay of Bengal positions Dhaka at the epicenter of Indo-Pacific talks. The unfettered access of Bangladesh to the Bay of Bengal has attracted geo-political interest in recent years. In response, Bangladesh has moved its strategic focus from land-based to maritime, with the Bay of Bengal serving as its ‘third neighbor,’ displaying its recognition and dedication to the Indo-Pacific. Foreign capital specialists continue to see Dhaka’s foreign policy via a geo-political lens despite Bangladesh assuming its role as an Indo-Pacific state. Bangladesh has opted to be a regional leader instead of joining the bloc. This context is vital for comprehending Dhaka’s forthcoming Indo-Pacific perspective.